Consumer Factors in Choosing Shopping Place in 4.0 - Dede Suleman; Hapzi Ali; Dewi Nusraningrum; Mochammad Mukti Ali (Program Studi Magister Manajemen FE Unsri, 2019)
Research Purpsoses – With the shipment analysis tool used, the results of this study show that education and income factors determine consumers in deciding where to shop in offline, online retail, or both.Methods – This research method is quantitative, while the sample in this study was conducted with non-probability sampling with the criteria respondents are consumers who have shopped fashion products through online, Respondents are from the age of 17 years. Respondents are those who live around the City of DKI Jakarta. The technique used in this research is purposive sampling method with the number n = 195.Results – In this study it can be concluded that the decision to choose where to shop for fashion products is strongly influenced by age, education, employment and income if the meaning of the output is drawn.Research limitations –In this study the decision of consumers to choose where to shop was influenced by factors of consumer characteristics namely education and income. Recommendations for further research are to use more methodological work and other variables.Originality/value – This research is focus on generations who are consumers, each generation has a different behavior where there is a generation X with an age range > 42 years, Generation Y with ages 21-41 years and Generation Z < 21 years Keywords : Consumer decisions, Demographics, Discriminant analysis.